Exchange-traded funds and real investment - ANTONIOU, Constantinos (Institutional Knowledge at Singapore Management University, 2023)
We investigate the link between exchange-traded funds and real investment. Cross-sectionally, higher ETF ownership is associated with an increased sensitivity of real investment to Tobin's q and a heightened ability of stock returns to forecast future earnings. Inclusion of stocks in industry ETFs enhances investment-q sensitivity and implies greater incorporation of earnings information into prices prior to public releases. Greater nonmarket ETF ownership leads to increased (reduced) reliance of real investment on own (peers') stock prices. Overall, the evidence is consistent with ETFs positively affecting real investment efficiency via greater flows of information.